Child-Turcotte-Pugh Class is Best at Stratifying Risk in Variceal Hemorrhage: Analysis of a US Multicenter Prospective Study. Issue 5 (May 2017) - Fortune, Brett E.; Garcia-Tsao, Guadalupe; Ciarleglio, Maria; Deng, Yanhong; Fallon, Michael B.; Sigal, Samuel; Chalasani, Naga P.; Lim, Joseph K.; Reuben, Adrian; Vargas, Hugo E.; Abrams, Gary; Lewis, Michele D.; et al.
Abstract : Goals/Background: Data on acute variceal hemorrhage (AVH) in the United States is limited and the best method to stratify risk is not clear. Taking advantage of a prospective US cohort study, we aimed to (1) describe clinical outcomes of AVH and their predictors; (2) compare predictors of 6-week mortality. Study: Prospective 15-center US cohort of patients with cirrhosis presenting with endoscopically proven AVH, all of whom received antibiotics, vapreotide (a somatostain analog) infusion and endoscopic band ligation. Patients were enrolled between August 2006 and April 2008. Primary outcome was 6-week mortality. Secondary outcome was 5-day treatment failure. The prognostic value of Child-Turcotte-Pugh (CTP) class, Model for End-stage Liver Disease (MELD) score and a recent recalibrated MELD were compared. Results: Seventy eligible patient were enrolled; 18 (26%) patients died within 6-weeks of index bleed. Demographic, clinical, and laboratory data were compared between survivors and nonsurvivors. Multivariate models showed that admission CTP or the MELD score (separately) were independent predictors of survival. The discriminative values of CTP (area under receiver operating characteristic: 0.75) and MELD (area under receiver operating characteristic: 0.79) were good and not significantly different ( P =0.27). However, calibration (correlation between observed and predicted mortality) test was significantly better for CTP than for MELD, with the recently described recalibrated MELD model having the worst agreement. Predicted mortality for CTP-A was <10%, CTP-B 10% to 30%; and CTP-C >33%. Conclusions: AVH mortality of 26% in the United States is in the upper range limit compared with recent series but may be due to inclusion of patients with more advanced cirrhosis. CTP score has the best overall performance in the prediction of 6-week mortality and is best at stratifying risk. Abstract : Supplemental Digital Content is available in the text.